Pengembangan Buku Ajar Interaktif Berbasis QR Code dan Short Link pada Mata Kuliah Praktik Kelistrikan Bodi - Ranu Iskandar; Rusiyanto Rusiyanto; Rizki Setiadi; , Khoirul Huda; Hanif Hidayat (Jurnal Ilmiah Wahana Pendidikan, 2023)
The body electricity course is a compulsory subject so it is necessary to innovate teaching materials to achieve learning goals. This study aims to (1) determine the validity of interactive textbooks based on qr code and short links in body electricity courses, (2) find out the practicality of using interactive textbooks based on QR code and short links in body electricity courses, and (3) find out the effectiveness of interactive textbooks based on QR codes and short links in body electricity courses. This research is R&D. The model used is 4D but only the define, design, and develop stages are carried out. The questionnaire uses 7 Likert scales. The research instrument proved its validity and reliability. The results of this study indicate that (1) interactive textbooks based on QR code and short links in body electricity courses from material experts while media experts are very valid at 94.63% and 95.39%, (2) interactive textbooks interactive textbooks based on QR code and short links in body electricity courses are very practical by 86.61%, and (3) interactive textbooks based on QR code and short links on body electricity courses are very effective by 86.43%. Based on the results of this study, it can be interpreted that the textbooks developed are feasible to be implemented in learning and disseminated.